Wpływ wybranych wskaźników makroekonomicznych na wyniki finansowe polskich spółek giełdowych - Urbański, Stanisław (Influence of Selected Macroeconomic Indexes on Financial Results of Companies Listed on the Polish Stock Exchange, 2007)
This paper presents a model describing the rates of changes of company financial results versus macroeconomic indexes. The research was carried out on the basis of securities traded on WSE in the period from 1995 to 2004. The model is based on the two-pass Fama-MacBeth procedure applied in testing CAPM. The time-series analysis in pass I determines loadings of explanatory variables and changes of functions LICZ and FUN. The functions are dependent on the financial results and market value of companies. A significant influence of chosen explanatory variables on LICZ and FUN is observed for most investigated portfolios. Cross-sectional regressions run in pass II examine the rate of changes of LICZ and FUN versus the changes of variable loadings determined in pass I. Non-zero values of pass II regression parameters and high R2 and F indexes support the proposed model.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 588-600